Dart and Arrow Points on the Columbia Plateau of Western North America. Issue 2 (20th April 2010) - Ames, Kenneth M.; Fuld, Kristen A.; Davis, Sara
Abstract : The timing of the bow and arrow's introduction, spread, and replacement of the atlatl is an important research question in North American prehistory. Although regional archaeologists have not focused on the issue, it is generally thought that the bow and arrow were introduced on the Columbia Plateau ca. 2, 300 years ago and completely replaced the atlatl by 1000 B.P. We apply two sets of discriminate functions and four threshold values to three large projectile point samples from the Columbia Plateau and a control sample from the Western Great Basin. Our results indicate that the atlatl was used on the Plateau by ca. 10, 800 B.P. While the bow and arrow may have been present by 8500 B.P., they were ubiquitous in the region by 4400 B.P. Atlatl use appears to have increased for a while after 3000 B.P. At the same time, metric differences between dart and arrow points strengthened. Darts became rare after 1500 B.P. but seem to have been in use in small numbers at least until contact.